Enhancing disaster management for human emergency evacuation using an integration of the social force model and agent-based simulations - Noor Akma, Abu Bakar; Musa Kabir, Ibrahim; Mohd Hanafiah, Ahmad; Che Akmal, Che Yahaya; Mazlina, Abdul Majid (GBMR, 2025)
Purpose: The purpose of this review study is to consolidate and evaluate existing research on flood and disaster evacuation modelling, with a specific focus on human behaviour during emergencies and the effectiveness of various simulation models. By utilizing secondary sources from published documents, the study aims to provide a comprehensive overview of current methodologies and their applications in disaster management. This review seeks to identify common themes, highlight significant findings, and uncover gaps in the literature to inform future research and improve the planning and execution of evacuation procedures. Ultimately, the study aims to enhance the understanding and propose effective evacuation strategies, contributing to increased public safety and more efficient disaster management practices. Design/methodology/approach: The methodology involves a comprehensive literature review of existing studies on flood and disaster evacuations, focusing on human behaviour during emergencies and the effectiveness of various simulation models. Relevant academic articles, books, and reports were identified through databases such as Google Scholar, PubMed, Scopus, Google Scholar and IEEE Xplore. Keywords used for the search included "flood evacuation", "disaster management", "human evacuation behavior”, “human evacuation", “human evacuation movement”, "Social Force Model", "Agent-Based Simulation," and "hybrid models". Findings: Synthesis of findings is from the extracted information to provide an overview of the current state of research on flood and disaster evacuation modelling. Particular attention was given to identifying common themes, gaps in the literature, and areas where further research is needed. The review included a critical analysis of the methodologies and findings of the selected studies. This involved assessing the strengths and limitations of different simulation models (e.g., SFM, ABS, hybrid models) and their applicability to various disaster scenarios. Research limitations/implications: The primary limitation of this review study is its reliance on secondary data from published documents rather than primary data collection. This approach may lead to the exclusion of recent, unpublished findings or emerging trends that are not yet documented in the literature. Additionally, the quality and comprehensiveness of the review are dependent on the availability and accessibility of relevant publications. While the study aims to provide a thorough overview, it may not capture all nuances and regional variations in human behaviour during evacuations. Future research could address these limitations by incorporating primary data collection and expanding the scope to include a broader range of sources. Practical implications: The findings of this review have significant practical implications for emergency planners, building designers, and policymakers. By synthesizing current knowledge on flood and disaster evacuation models, the study provides insights into effective strategies for managing evacuations in various scenarios. The critical analysis of different simulation techniques (SFM, ABS, hybrid models) offers guidance on selecting appropriate models for specific applications, enhancing the planning and execution of evacuation procedures. This information can help optimize resource allocation, design safer buildings, and develop more efficient evacuation plans, ultimately improving public safety during emergencies. Originality/value: This review paper offers a valuable contribution to the field of disaster management by consolidating and critically evaluating existing research on evacuation modelling. The use of secondary data allows for a broad perspective on established methodologies and their effectiveness, providing a comprehensive overview that is not limited by the constraints of primary data collection. The study highlights the strengths and limitations of various simulation models, offering a nuanced understanding of their applicability in different disaster scenarios. This review serves as a resource for researchers and practitioners, fostering informed decision-making and encouraging further research to address identified gaps and emerging challenges in evacuation modelling.